The influence of students' working memory capacity on solving calculus problems - A, Ruslimin; Fuad, Yusuf; Masriyah, Masriyah (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the influence of students' working memory capacity (WMC) on their ability to solve calculus problems, particularly within the topic of integral calculus. A total of 98 undergraduate mathematics education students from a state Islamic college in Makassar, Indonesia, participated in this quantitative study. Data were collected using two validated instruments: a modified complex span task (CST) to assess WMC, and a calculus problem test (CPT) to evaluate calculus problem-solving performance. Statistical analyses, including t-tests, F-tests, regression modeling, and the coefficient of determination, revealed a significant positive relationship between WMC and calculus problem-solving ability, with WMC accounting for 74.5% of the variance in students’ performance. The results show that students with higher WMC outperformed those with lower WMC on complex calculus tasks, indicating that WMC plays a critical role in mathematical cognition. These findings underscore the need for educators to consider cognitive load and individual memory capacity when designing instructional strategies. Practical implications suggest incorporating cognitive training and tailored scaffolding into the curriculum to support students with lower WMC. The study contributes new insights by focusing specifically on integral calculus—a domain rarely examined in WMC research—highlighting the importance of cognitive resources in advanced mathematics learning.